Investigating the Optical Properties of a Laser Induced 3D Self‐Assembled Carbon–Metal Hybrid Structure. Issue 18 (8th April 2019) - Butt, Muhammad Abdullah; Lesina, Antonino Calà; Neugebauer, Martin; Bauer, Thomas; Ramunno, Lora; Vaccari, Alessandro; Berini, Pierre; Petrov, Yuriy; Danilov, Denis; Manshina, Alina; Banzer, Peter; Leuchs, Gerd
Abstract: Carbon‐based and carbon–metal hybrid materials hold great potential for applications in optics and electronics. Here, a novel material made of carbon and gold–silver nanoparticles is discussed, fabricated using a laser‐induced self‐assembly process. This self‐assembled metamaterial manifests itself in the form of cuboids with lateral dimensions on the order of several micrometers and a height of tens to hundreds of nanometers. The carbon atoms are arranged following an orthorhombic unit cell, with alloy nanoparticles intercalated in the crystalline carbon matrix. The optical properties of this metamaterial are analyzed experimentally using a microscopic Müller matrix measurement approach and reveal a high linear birefringence across the visible spectral range. Theoretical modeling based on local‐field theory applied to the carbon matrix links the birefringence to the orthorhombic unit cell, while finite‐difference time‐domain simulations of the metamaterial relates the observed optical response to the distribution of the alloy nanoparticles and the optical density of the carbon matrix. Abstract : A novel carbon–metal hybrid crystalline material, fabricated using a laser‐induced deposition process, is investigated experimentally and theoretically for its optical properties. It exhibits, amongst other interesting properties, a very pronounced linear optical birefringence as a direct consequence of the orthorhombic carbon lattice. The carbon lattice, intercalated with plasmonic Au–Ag nanoparticles, holds immense potential for opto‐electronics, nanophotonic experiments, and applications.